Development of E-Modules Based on PBL (Problem Based Learning) Integrated with STEM (Science, Technology, Engineering, Mathematic) on Thermochemistry Material - Aprili Safitri Pardosi; Ratu Evina Dibyantini (Jurnal Pendidikan dan Pembelajaran Kimia, 2025)
Development of E-Modules Based on PBL (Problem Based Learning) Integrated with STEM (Science, Technology, Engineering, Mathematic) on Thermochemistry Material. This study aims to determine the level of feasibility (validity) of the PBL-based e-module (Problem Based Learning) integrated with STEM (Science, Technology, Engineering, Mathematic) developed on Thermochemistry material. This type of research is development research using the 4D development model which consists of the define, design, develop, and disseminate stages, but is limited to the 3D model, namely develop. After processing the data on the validation sheet, the average validation of the material expert was 89% and the average validation of the media expert was 89% so that it was included in the very valid category. The research conclusion interpreted from the results of data processing obtained is that the PBL-based e-module integrated STEM on thermochemistry material developed is very valid or very feasible to use.